A descriptive study on the medical emergency knowledge, drugs and equipment of UPCD clinicians and the U.P. College of Dentistry - Yangco, Raquel C.; Serraon, Antolin (Adviser).
The primary objective of this study is to determine the medical emergency knowledge of U.P. Collge of Dentistry clinicians and the available drugs, and equipment in the UPCD . Fifty-nine questionnaires were distributed to the junior and senior clinicians. Forty-five of these questionnaires were useable. The questionnaire inquired about various medical emergency topics such as the awareness of clinicians regarding the existing medical emergency drugs and equipment, unconsciousness, respiratory distress, metabolic disorders, seizures, hemorrhage, drug-related emergencies, chest pain, and Cardiopulmonary Resuscitation (CPR). A total of 21 (46.7%) of the subjects did not reach the 75% mark while 24 (53.3%) of the subjects garnered a score of 75% and above. The drugs and equipment was checked by the researcher at the Oral Surgery Department of the UPCD. The researcher concluded that the medical emergency knowledge of UPCD clinicians needs to be improved since a significant number of the subjects did not reach the 75% mark. The drugs and equipment needs upgrading and periodic checking since a number of them are either non-existing or are already expired.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.